Influence of Temperature Variations on Growth of Nostoc (Cyanobacteria) HS-5 and HS-20 Isolated from Indonesian Hot Springs - NINING BETAWATI PRIHANTINI; CAHYA GUSLYANI; RATNA YUNIATI; WELLYZAR SJAMSURIDZAL (Microbiology Indonesia, 2018)
The research aims to know the effect of variation temperature to the growth of Nostoc HS (Hot Spring)-5 and HS-20. Strain of Nostoc HS-5 was isolated from Ciseeng hot spring which has habitat temperature range of 30-43 °C, and Nostoc HS-20 was isolated from Pancar Mountain hot spring which has temperature range of 46-69 °C. The research was done by measuring biomass weight and chlorophyll content on day-1, 2, 3, 4, 7, 10, 14, 17, and 21. The temperatures used were 20 °C, 35 °C, and 50 °C. The growth medium used was Bold Basal Medium (BBM) with pH 6.6. Each treatment was made in four replications. Non-parametric statistical analysis used were the Friedman test (a=0.05) and Spearman test (a=0.01).The result showed there were significant differences on the biomass weight of Nostoc HS-5 and HS-20 grown at temperature of 20 °C, 35 °C, and 50 °C. The average amount of biomass highest weight for Nostoc HS-5 and HS-20 occurred in both strains were grown at 35 °C.  Besides that, there was no correlation between the weight of biomass and chlorophyll content of Nostoc HS-5 and HS-20.